Restoration of Livestock Services in Conflict and Drought Affected Areas of Ethiopia (RESTORE): Laboratory Mapping Tool (LMT) core application training report - Alemayehu, Gezahegn; Alemu, Biruk G. (International Livestock Research Institute, 2025)
Launched in November 2024, the Restoration of Livestock Services in Conflict and Drought-Affected Areas of Ethiopia (RESTORE) Project, is a European Union (EU)-supported initiative that aims to enhance food security, nutrition, and livelihood resilience in Ethiopia, particularly in regions affected by conflict and drought–the Tigray, South Ethiopia, and Somali regions. Parallel initiatives of the project are also underway in the existing EU-funded Individual Measure 3 (IM3) regions, including Amhara, Oromia, and Somali. As part of the effort to restore the livestock service delivery, the project focuses on equipping and upgrading the regional animal health laboratories to strengthen disease surveillance and control activities. Before this intervention, the baseline assessment of these laboratories is necessary so that progress and impact during and after the intervention can be measured against this baseline. For this purpose, the Laboratory Mapping Tool (LMT), developed by the Food and Agriculture Organization of the United Nations (FAO) has been adopted to assess the functionality and capacity of veterinary laboratories and improve their standards. A one-day training workshop was conducted to strengthen the capacity of regional laboratory personnel on the use and application of the LMT core application. The training aimed to standardize and harmonize laboratory assessments across 10 regional veterinary laboratories and establish a baseline for future RESTORE project interventions.